Penerapan Metode Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) dalam Seleksi Penerimaan Peserta Kegiatan Program Pendidikan Kecakapan Wirausaha - Fazlur Rahman; Abdi Harfani; Mesran; Kelik Sussolaikah; Nelly Khairani Daulay; Ronal Watrianthos (Journal of Informatics Management and Information Technology, 2023)
The Entrepreneurial Skills Education Program (PKW), is one of the programs from the Ministry of Education and Culture in 2019. PKW is an educational service through courses and training to provide knowledge, skills, and foster an entrepreneurial mental attitude in managing self-potential and the environment as a basis for entrepreneurship. This study aims to select the acceptance of participants in the Entrepreneurial Skills Education (PKW) program. The method used in the selection is by applying the MOORA method. The MOORA method is a method with very simple steps. The results showed that A1 is the best compared to several other alternatives with a value of 0.304